Mobile Augmented Reality Berbasis Sistem Android Sebagai Supplemen Belajar Yang Meningkatkan Keterampilan Penggunaan Media Digital Guru - Rini, Daniar Setyo; Eka Putri Azrai; Putri Riupassa, Afifah Shabrina; Hanna Rosmawati; Juwita Tamherwarin; Indang Sriayu Yulidianti Roditya (Jurnal SOLMA, 2023)
Background: The development of technology in education and teaching requires teachers to have skills in making and using technology as a learning medium, learning resource or learning supplement. ARSINAPS is an Augmented Reality learning media based on the android system that has been developed in order to help teachers to be able to visualize the structure of the tissues that make up the respiratory system with three-dimensional objects. The skill of using digital media for teachers certainly needs to start with workshop activities and socialization of digital learning media.Thus, in order to improve the skills of using digital media, this P2M activity was carried out by introducing ARSINAPS as an AR learning supplement product and also providing training to be able to make AR media simply. Method: The training was attended by 20 biology teachers from MGMP Bekasi district, West Java and the implementation of the activity was carried out at SIT Ulil Albab, Bekasi. Results: Skills in using digital media as a medium and learning supplement increased after the introduction and training on making Android-based Augmented Reality media. The average N-Gain score is 7.13 and is in the high category. Conclusion: Teachers are motivated and can already use Augmented Reality-based learning media as a supplement to learning in schools.